An Investigation into the Utilization of Swarm Intelligence for the Design of Dual Vector and Proportional–Resonant Controllers for Regulation of Doubly Fed Induction Generators Subject to Unbalanced Grid Voltages - Reddy, Kumeshan; Saha, Akshay Kumar (Energies (Basel), 2022)
This work presents an investigation into the use of swarm intelligence techniques for the control of the doubly fed induction generator under unbalanced grid voltages. Swarm intelligence is a concept that was introduced in the late 20th century but has since undergone constant evolution and modifications. Similarly, the doubly fed induction generator has recently come under intense investigation. Owing to the direct grid connection of the DFIG, an unbalanced grid voltage harshly impacts its output power. Established mitigation measures include the use of the dual vector and proportional–resonant control methods. This work investigates the effectiveness of utilizing swarm intelligence for the purpose of controller gain optimization. A comparison of the application of swarm intelligence to the dual vector and proportional–resonant controllers was carried out. Three swarm intelligence techniques from across the timeline were utilized including particle swarm optimization, the bat algorithm, and the gorilla troops optimization algorithm. The system was subject to single-phase voltage dips of 5% and 10%. The results indicate that modern swarm intelligence techniques are effective at optimizing controller gains. This shows that as swarm intelligence techniques evolve, they may be suitable for use in the optimization of controller gains for numerous applications.